Pembelajaran Aksesibilitas Pendidikan Agama Islam (PAI) Bagi Anak Berkebutuhan Khusus - Hikmah, Badiatul (Yayasan Letiges Konsultan Sosial, 2024)
Learning for children with special needs requires special skills. Apart from delivering learning, a teacher must also be able to observe the unique talents and interests of special needs children. This research aims to analyze the implementation of Islamic religious education accessibility learning for children with special needs. This research was conducted at SD Al Kautsar Pasuruan. This research uses a qualitative case study type approach. Collecting data through observation techniques, interviews and document study. To analyze the data using qualitative analysis techniques, data presentation, data reduction, and conclusion. The analysis found that accessibility in PAI teaching is the key to providing equal opportunities for all individuals, including people with disabilities, to experience and understand their Islamic religion. Implementing PAI learning at SD Al Kautsar Pasuruan for children with special needs requires an inclusive approach. To create an inclusive approach, it is necessary to understand the needs and characteristics of various children. This can be done by doing curriculum adjustments, collaboration with exceptional education specialists, using educational technology, inclusive learning approaches and field observations as reference data in implementing PAI learning for children with special needs.